As pessoas com SIDA e seus familiares : interpretações do adoecimento - Silva, Fábio Cabral da (2013)
The Acquired Immunodeficiency Syndrome (AIDS) emerged in the 80s, causing uproar in society, for its high fatality rate and rapid spread, as well as the lack of control by modern science, eventually be characterized as a historical event atypical. This lack of knowledge surrounding AIDS mobilized the scientific community in order to understand its mechanism of pathogenicity to control/mitigate its lethality. Thus, it was developed a wide range of research focused on aspects biopathological AIDS, which guided the organization of health services, as well as professional practices to meet people living with this disease. In this process, the issues regarding the relations of everyday life of the people did not receive the required value by health professionals. It is necessary to pay attention that the illness is related to the social environment, social relations woven by people in the process of life, permeated by shared meanings in the social groups to which they belong, is a social and cultural construct. Therefore, the objective of this study is to understand the interpretation of illness from AIDS in the vision of people with this condition and their families. With this in mind, the present investigation was constituted in a qualitative study, in which they sought to pay attention to the phenomenon in its intensity, with the case study as a research strategy, operationalized by open interview. The data collection took place in a university hospital in the city of Cuiabá, Mato Grosso, and had three people affected by AIDS and two family members as research subjects. The corpus analysis was organized from the Content Analysis, in thematic modality. The results of our research have enabled the development and understanding of the disease AIDS to affected individuals and their families, subsidizing the production of two articles: “The influence of time and social relations in the meanings of illness by AIDS” and “The falling ill in the Acquired Immunodeficiency Syndrome: the movements made by the patients and their families in seeking health care”. The study showed that the trajectory of life of these people is surrounded by striking events that permeate the discovery of diagnosis, causing the rupture in their lives, as well as the manifestations of AIDS, that print limitations and restrictions to patients. These processes are characterized as peculiar events, interpreted and reinterpreted according to the sociocultural contexts in which they live, suffering the influence of the dimensions of time and social relations. Thus, the disease AIDS transcends the condition of having a disease that only affects the person's immune system, it also refers to the daily confrontation of prejudice and stigma from society. Finally, it is envisaged that this study will contribute to the consolidation of knowledge specific to the science of nursing, with elements that enhance the looks on their object of study, nursing care, thereby giving subsidies to think the health careand nursing to people living with this chronic condition.